Safety evaluation of aqueous extract from Eugenia uniflora leaves: Acute and subacute toxicity and genotoxicity in vivo assays. (15th November 2022) - Assunção Ferreira, Magda Rhayanny; Daniele-Silva, Alessandra; de Almeida, Lucas Ferreira; Felipe dos Santos, Ewelyn Cintya; Barbosa Machado, Janaina Carla; Macário de Oliveira, Alisson; de Freitas Fernandes Pedrosa, Matheus; Guedes Paiva, Patrícia Maria; Napoleão, Thiago Henrique; Lira Soares, Luiz Alberto
Abstract: Ethnopharmacological relevance: Eugenia uniflora Linn (Myrtaceae) is the native species of Brazil. The leaves of this species are used in folk medicine to treat different inflammatory and gastrointestinal disorders. However, research on the safety of using E. uniflora leaves has been poorly explored. Aim of the study: This approach aims to investigate the phytochemical composition as well as the acute, subacute toxicity, and in vivo genotoxic profile of the aqueous extract of E. uniflora leaves. Materials and methods: The chemical composition of E. uniflora leaf extract was determined by Fingerprint by High-Performance Thin Layer and High-Performance Liquid Chromatography . The acute toxicity in vivo was evaluated for 14 days after the administration of E. uniflora leaves extract (2000 mg/kg). For the evaluation of subacute toxicity, mice were daily treated for 28 days with E. uniflora extract (250, 500, or 1000 mg/kg). Signs of behavioral toxicity and biochemical and hematological alterations, including the multiple organ toxicities were investigated. In addition, the micronucleus assay was used to evaluate the in vivo genotoxicity of the leaves extract in murine erythrocytes . Results: The phytochemical analysis showed the majority presence of phenolic compounds (gallic acid, ellagic acid, and myricitrin). Single or repeated doses of the aqueous extract of E. uniflora leaves did not reveal any signs of in vivo toxicity . Daily doses of the extract for 28 days induced a slight reduction in cholesterol and triglyceride levels. Furthermore, E. uniflora leaves extract (1000–2000 mg/kg) showed no genetic damage in the micronucleus assay, indicating the absence of genotoxicity of the herbal species. Conclusion: The aqueous extract of E. uniflora leaves showed a predominance of phenolic compounds, with non-toxic and non-genotoxic action in vivo . This approach sheds light on the chemical composition of the leaves of E. uniflora and suggests a high margin of safety in the popular use of the leaves of this plant species. Graphical abstract: Image 1 Highlights: The phytochemical analysis showed the presence of phenolic compounds. A single and repeated doses of the E. uniflora extract did not reveal any signs of toxicity in vivo . A slight reduction in cholesterol and triglyceride levels was observed. The results suggest a margin of safety in the popular use E. uniflora leaves.